Functional Diversity of Quorum Sensing Receptors in Pathogenic Bacteria: Interspecies, Intraspecies and Interkingdom Level - Khan, Fazlurrahman; Javaid, Aqib; Kim, Young-Mog (Current Drug Targets, 2019)
The formation of biofilm by pathogenic bacteria is considered as one of the most powerful mechanisms/modes of resistance against the action of several antibiotics. Biofilm is formed as a structural adherent over the surfaces of host, food and equipments etc. and is further functionally coordinated by certain chemicals produced itself. These chemicals are known as quorum sensing (QS) signaling molecules and are involved in the cross talk at interspecies, intraspecies and interkingdom levels thus resulting in the production of virulence factors leading to pathogenesis. Bacteria possess receptors to sense these chemicals, which interact with the incoming QS molecules. It is followed by the secretion of virulence molecules, regulation of bioluminescence, biofilm formation, antibiotic resistance development and motility behavioral responses. In the natural environment, different bacterial species (Gram-positive and Gram-negative) produce QS signaling molecules that are structurally and functionally different. Recent and past research shows that various antagonistic molecules (naturally and chemically synthesized) are characterized to inhibit the formation of biofilm and attenuation of bacterial virulence by blocking the QS receptors. This review article describes about the diverse QS receptors at their structural, functional and production levels. Thus, by blocking these receptors with inhibitory molecules can be a potential therapeutic approach to control pathogenesis. Furthermore, these receptors can also be used as a structural platform to screen the most potent inhibitors with the help of bioinformatics approaches.
Keywords: inhibitor